Wind-sand tunnel testing of surface-mounted obstacles: Similarity requirements and a case study on a Sand Mitigation Measure. Issue 214 (July 2021) - Raffaele, Lorenzo; van Beeck, Jeroen; Bruno, Luca
Abstract: Windblown sand flow interacts with a number of surface-mounted human-built obstacles. The wind-sand flow perturbation and resulting morphodynamic response of the sand bed cannot be assessed in analytical terms. Therefore, wind-sand tunnel studies around scale physical models are often carried out. They should be driven by physical similarity theory based on dimensionless numbers referred to the whole multiphase and multiscale flow. However, similarity requirements cannot be fully satisfied under typical testing conditions and attention should be paid on the extent of the similarity relaxation. In this study, the background of wind-sand tunnel testing of surface-mounted obstacles is recalled by reviewing wind tunnel setups and similarity requirements. Then, a wind-sand tunnel campaign on a Sand Mitigation Measure is described and critically discussed. The setup dimensionless numbers are compared with statistics on those of past studies. The inescapable relaxation of similarity requirements is motivated by the test goals. The time evolution towards in-equilibrium conditions of both sand bed morphodynamics and sand transport is discussed. Finally, the results of engineering interest are described: the Sand Mitigation Measure sand trapping performance is assessed in dimensionless terms through the measurements of the incoming and outgoing sand concentration in air. Highlights: Wind-Sand Tunnel Tests are categorized based on obstacle types and setup conditions. Similarity requirements are reviewed and their relaxation is critically discussed. In-equilibrium conditions around the tested Sand Mitigation Measure are analysed The aerodynamic working principle is confirmed through sand bed morphodynamics. Sand trapping performance is assessed by a dimensionless sedimentation coefficient.